IMPLEMENTASI SDGs MELALUI KEGIATAN SERUPAH (Serentak Pungut Sampah) PADA ANAK SEKOLAH DASAR - Kharisna, Feby; Maryani, Ika; Hidayanthi, Rahma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Global sustainability challenges demand behavioral change from an early age, including through education at the elementary school level. This study discusses the implementation of the Sustainable Development Goals (SDGs) through the SERUPAH (Serentak Pungut Sampah) program for elementary school students. The research employs a qualitative method with a naturalistic observation approach to gain an in-depth understanding of the SERUPAH program implementation, which includes several key stages: introduction to waste and its management, practical activities in collecting and sorting waste, cooperation, student interaction and enthusiasm, challenges related to infrastructure and external limitations, as well as a review of the waste collection and sorting activities. The findings show that the program effectively enhances students’ understanding of different types of waste and their environmental impact, encourages active participation in maintaining cleanliness, and fosters environmental awareness and social responsibility. The SERUPAH program has proven to support the achievement of the SDGs, particularly in environmental education and sustainable development from an early age.